2022
DOI: 10.21203/rs.3.rs-1957640/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabarcoding Inventory of an Arctic Tundra Soil Ecosystem Reveals Highly Endemic Communities

Abstract: Biodiversity surveys of Arctic soil ecosystems are limited. Here, we provide a sequence-based inventory of soil fauna from an Arctic tundra ecosystem near Iqaluktuutiaq (Cambridge Bay), Nunavut. Invertebrate communities were extracted from soil at three sites with vegetation cover and three non-vegetated sites and inventoried using 18S metabarcode sequencing. A total of 361 Amplicon Sequence Variants (ASV) were identified and assigned to the closest matching taxonomic orders, most of which belonged to the Nema… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 67 publications
(47 reference statements)
0
4
0
Order By: Relevance
“…Our results support the idea that large-scale variation in litter decomposition can be explained by macro-scale temperature conditions (Swift et al 1979, Davidson and Janssens 2006, Keuskamp et al 2013 https://www.zotero.org/google-docs/?broken=xgn2Za, but indicated that variation in soil moisture and active layer thickness play a greater role at the landscape scale. While we detected no significant interactions between soil moisture and thermal sum at this location, as the tundra continues to change under warming climates and shifting weather regimes, examining relationships between temperature, soil moisture and active layer depth and decomposition remains an important step in further research (Tao et al 2019, Jorna et al 2022.…”
Section: Soil Moisture Explained More Variation In Decomposition Than...mentioning
confidence: 74%
See 3 more Smart Citations
“…Our results support the idea that large-scale variation in litter decomposition can be explained by macro-scale temperature conditions (Swift et al 1979, Davidson and Janssens 2006, Keuskamp et al 2013 https://www.zotero.org/google-docs/?broken=xgn2Za, but indicated that variation in soil moisture and active layer thickness play a greater role at the landscape scale. While we detected no significant interactions between soil moisture and thermal sum at this location, as the tundra continues to change under warming climates and shifting weather regimes, examining relationships between temperature, soil moisture and active layer depth and decomposition remains an important step in further research (Tao et al 2019, Jorna et al 2022.…”
Section: Soil Moisture Explained More Variation In Decomposition Than...mentioning
confidence: 74%
“…We did not investigate soil fauna or microbial activity in this study, but soil fauna presence, which increases litter decomposition, is globally driven by both soil moisture content (Thakur et al 2018) and global temperature patterns (Wall et al 2008). Tundra soil fauna populations can be spatially heterogeneous and linked to microhabitats and vegetation (Tao et al 2019, Jorna et al 2022). We did however, observe fungal biomass in soils during the extraction of our tea bags in some locations, suggesting that the below‐ground biotic environment could be an important factor explaining litter decomposition across this study system.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations